COMPARATIVE ANALYSIS OF EMPLOYEES’ PERSPECTIVE ON ASSET-LIABILITY MANAGEMENT IN BANKS - Tanwar, Jyoti; Vaish, Arun Kumar; Rao, NVM (Indian Journal of Finance and Banking, 2022)
Asset-Liability Management is critical for the successful working of banks. The Indian Financial system is very dynamic and growing rapidly. Banks focus on both the assets and liabilities due to liquidity risk, interest rate risk and foreign exchange risk. The implementation and understanding of ALM policies, and procedures will provide insight into the approach of banks towards ALM. A primary survey is conducted among employees of twelve public and twelve private banks to collect data related to employees’ experience, understanding, and knowledge about the ALM. The questionnaire used in the study carries Yes/No type questions, multiple-choice questions, checklist questions, scaled questions. The data is analyzed using SPSS. The results suggest that public and private banks’ employees have a similar understanding and knowledge of the ALM. Both types of banks follow identical practices and policies in the implementation of ALM with few deviations. The employees of the banks were hesitant to answer complex questions, and therefore questionnaire has to be kept generic and straightforward. This paper studies ALM in banks using primary data. All other studies have been conducted using secondary data or literature surveys. These studies did not feature the banks’ approach in ALM policies, practices, and procedures. JEL Classification Codes: E58, E43, G33, G32, D81.